2019
DOI: 10.1177/1539449219859935
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Telehealth-Delivered Home Safety Evaluations for Caregivers of Clients With Dementia

Abstract: Video telehealth can increase access to home-based care, thus allowing older adults to maintain functional independence and age-in-place. This is particularly salient for persons with dementia whose cognitive changes increase home safety risk. Little is known about the technological and safety challenges of in-home assessment via video. This feasibility study explored the process and resource requirements of a remotely delivered telehealth occupational therapy home safety evaluation from a Veterans Health Admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 24 publications
0
34
0
1
Order By: Relevance
“…Indeed, a recent study estimated that 38% of Medicare beneficiaries were unready to engage in home telehealth 19 . However, when given the opportunity, many older patients can effectively engage in telehealth 13,20‐25 . We hypothesized that telehealth might improve access to care, but we were unsure if our patients were interested or if they had the technology and confidence to attempt a home telehealth visit 1 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a recent study estimated that 38% of Medicare beneficiaries were unready to engage in home telehealth 19 . However, when given the opportunity, many older patients can effectively engage in telehealth 13,20‐25 . We hypothesized that telehealth might improve access to care, but we were unsure if our patients were interested or if they had the technology and confidence to attempt a home telehealth visit 1 …”
Section: Introductionmentioning
confidence: 99%
“…19 However, when given the opportunity, many older patients can effectively engage in telehealth. 13,[20][21][22][23][24][25] We hypothesized that telehealth might improve access to care, but we were unsure if our patients were interested or if they had the technology and confidence to attempt a home telehealth visit. 1 We were specifically interested in telehealth visits that occurred in patients' homes, with synchronous audio and video.…”
mentioning
confidence: 99%
“…All variables sorted by Veteran MMSE. Identification numbers listed are from our manuscript relate to technical feasibility (Gately et al, 2020). Three of the four instances of lower caregiver satisfaction (disagree or strongly disagree) for caregivers 8, 9, and 10 appeared to relate to the environmental factor of technological glitches.…”
Section: Discussionmentioning
confidence: 94%
“…The primary aims of the initial study were to examine feasibility of the telehealth encounter. Complete study details are reported elsewhere ( Gately et al, 2020 ). Here we examine caregiver satisfaction with the video telehealth home safety evaluation, through in-depth examination of caregiver satisfaction relative to person, environment, and occupation (PEO) factors.…”
Section: Methodsmentioning
confidence: 99%
“…Neither CST and CCI incorporate home evaluations in their interviews; occupational therapists can use telehealth to communicate with a client from a different location. This delivery of care can address the clients' natural environment, while reducing staff travel (Gately, Trudeau, & Moo, 2020).…”
Section: Implications For Otmentioning
confidence: 99%